Pravovoi status Olimpiiskogo komiteta Rossii - Voronin, S. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The registration of the Russian Olympic committee legal status according to the Russian legislation is caused by the rule of the item 5 of the rule 32 of the Olympic charters says, that as national Olympic committee the International Olympic committee can recognise only the organisation, which jurisdiction coincides with rules of the country, in which it is based and where its senior management is. "The Concurrence to rules of the country" should prove to be true by the act of the state registration of a organisation, which importance is, that as such act admit lawful its creation, and also the opportunity of the fulfilment of the further actions stipulated by its constituent documents, for achievement of the purposes of organisation. Taking into account the plurality of the special statuses, representing the scientific interest and legislative relations of the ROC, not examined within the framework of this research each of the legal statuses, deserves the separate study as considered by the author.